Moderating roles of user’s intention to use LINE official account in healthcare context: body mass index - Trakulmaykee, Numtip; Choksuchat, Chidchanok; Jetwanna, Korakot Wichitsa-nguan; Inthanuchit, Kochakorn Sukjan (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This study aimed to investigate the extended factors based on the technology acceptance model, and the moderating roles of customer behavioral intention factors to use information technology. This research is a questionnaire-based survey with convenience sampling approach where 386 cases were collected from healthcare customers. For statistical analysis, the study used SmartPLS as a tool for regression analysis and descriptive statistics. The findings revealed the influence of social norm on customer behavioral intention to use information technology in the healthcare context as significant factors at 0.001. In addition, the results indicated the small effect of two moderating variables in the proposed model. First, the problematic body mass index (BMI) can be a moderator on the relationship between social norm and customer behavioral intention to use technology at a significant level of 0.05. Second, the technology experience can moderate the relationship between perceived ease of use and customer behavioral intention to use technology at a significant level of 0.05. The proposed model may guide for future exploration, especially information services in healthcare businesses and developers.